Capture of an external anion beam into a linear Paul trap - Cerchiari, Giovanni; Erlewein, S.; Yzombard, Pauline; Zimmermann, M.; Kellerbauer, A. (Journal of physics. B, Atomic, molecular and optical physics, 2019)
We describe a linear Paul trap and high-voltage platform specifically designed for the trapping of a large and pure sample of anions from an external keV-energy beam. Capture and confinement in a static configuration of DC potentials was found to occur by transfer of axial to radial ion momentum due to elastic and inelastic collisions. Stability diagrams both in transmission and capture mode were recorded. The trapping efficiency was observed to be very sensitive to the axial potentials relative to the beam energy. Several 104 oxygen anions were loaded from a 2 keV primary beam and confined for several 100 s. Identification of trapped O− ions and contaminants was achieved by selective laser photodetachment.